Vaccines for Leprosy and Tuberculosis: Opportunities for Shared Research, Development, and Application - Coppola, Mariateresa; van den Eeden, Susan J. F.; Robbins, Naoko; Wilson, Louis; Franken, Kees L. M. C.; Adams, Linda B.; Gillis, Tom P.; Ottenhoff, Tom H. M.; Geluk, Annemieke (Frontiers in Immunology, 2018)
Tuberculosis (TB) and leprosy still represent significant public health challenges, especially in low- and lower-middle-income countries. Both poverty-related mycobacterial diseases require better tools to improve disease control. For leprosy, there has been an increased emphasis on developing tools for improved detection of infection and early phases of disease. For TB, there has been a similar emphasis on such diagnostic tests, while increased research efforts have also focussed on the development of new vaccines. BCG (Bacille Calmette-Guérin), the only available TB-vaccine, provides insufficient and inconsistent protection to pulmonary TB in adults. The impact of BCG on leprosy, however, is significant, and the introduction of new TB vaccines that might replace BCG could, therefore, have serious impact also on leprosy. Given the similarities in antigenic makeup between the pathogens M. tuberculosis (Mtb) and M. leprae, it is well possible, however, that new TB vaccines could cross-protect against leprosy. New TB subunit vaccines currently evaluated in human phase I and II studies indeed often contain antigens with homologues in M. leprae. In this review, we discuss pre-clinical studies and clinical trials of sub-unit or whole mycobacterial vaccines for TB and leprosy and reflect on the development of vaccines that could provide protection against both diseases. Furthermore, we provide the first preclinical evidence of such cross-protection by Ag85B (Mtb Antigen 85B)-ESAT6 (Early Secretory Antigenic Target) fusion recombinant proteins in in vivo mouse models of Mtb and M. leprae infection. We propose that preclinical integration and harmonization of TB and leprosy research should be considered and included in global strategies with respect to cross-protective vaccine research and development.